1978
DOI: 10.1001/archderm.114.8.1231
|View full text |Cite
|
Sign up to set email alerts
|

Transepithelial elimination of cutaneous chromomycosis

Abstract: the papillary dermis, but the pathogenetic mechanism for TE is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

1980
1980
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 0 publications
1
23
0
1
Order By: Relevance
“…The black dots seen on the surface of the lesions are a consequence of damaged connective tissue, foreign matter, and the fungal etiologic agents in the dermis being expelled through the epidermis [8,9]. Both patients described here had cerebriform lesions studded with black dots, which was suggestive of chromoblastomycosis.…”
Section: Discussionmentioning
confidence: 67%
“…The black dots seen on the surface of the lesions are a consequence of damaged connective tissue, foreign matter, and the fungal etiologic agents in the dermis being expelled through the epidermis [8,9]. Both patients described here had cerebriform lesions studded with black dots, which was suggestive of chromoblastomycosis.…”
Section: Discussionmentioning
confidence: 67%
“…Transepidermal elimination in chromoblastomycosis was originally studied by Batres et al (1978) when those authors were conducting a histopathological review of two cases of the disease and observed the presence of fungal structures in the stratum corneum (Figure 4). 17 The phenomenon of transepidermal elimination was confirmed in the patients in the present study.…”
Section: 16mentioning
confidence: 99%
“…The lesions are usually located commonly in the hands, forearms and ankles. Transepithelial elimination, a spontaneously oc curring dermoepidermal phenomenon, is an important process in the pathology of chromoblastomycosis [16], and probably results in the 'black dots' found on the lesion surface [2], These contain the sclerotic bodies as well as clotted blood, medlar bodies, chromobodies, chlamydospores, copper pennies, and sclerotic bodies described by various other mycologists.…”
Section: Commentmentioning
confidence: 99%